An exceptionally preserved association of complete dinosaur skeletons reveals the oldest long-necked sauropodomorphs. (30th November 2018) - Müller, Rodrigo Temp; Langer, Max Cardoso; Dias-da-Silva, Sérgio
Abstract : The rise of sauropodomorphs is still poorly understood due to the scarcity of well-preserved fossils in early Norian rocks. Here, we present an association of complete and exceptionally well-preserved dinosaur skeletons that helps fill that gap. They represent a new species, which is recovered as a member of a clade solely composed of Gondwanan Triassic taxa. The new species allows the definition of a set of anatomical changes that shaped sauropodomorph evolution along a period from 233 to 225 Ma, as recorded in the well dated Late Triassic beds of Brazil. In that time span, apart from achieving a more herbivorous diet, sauropodomorph dinosaurs increased their size in a ratio of 230% and their typical long neck was also established, becoming proportionally twice longer than those of basal taxa. Indeed, the new dinosaur is the oldest-known sauropodomorph with such an elongated neck, suggesting that the ability to feed on high vegetation was a key trait achieved along the early Norian. Finally, the clustered preservation mode of the skeletons represents the oldest evidence of gregarious behaviour among sauropodomorphs.